Comparison of Evidence-Based Treatment Protocols for Complex Trauma in Middle Eastern Conflict Populations - Luthfiah Mawar; M. Agung Rahmadi; Helsa Nasution; Nurzahara Sihombing (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
This meta-analysis systematically evaluates the relative effectiveness of various empirically supported therapeutic protocols designed to address complex trauma in populations affected by armed conflict in the Middle Eastern region. From 1,284 articles identified, 47 studies (N=4,832) met the inclusion criteria and were further analyzed. The primary findings indicate that Trauma-Focused Cognitive Behavioral Therapy (TF-CBT) produces the most significant therapeutic impact (g=0.83, 95% CI [0.76, 0.90], p<.001), followed by Eye Movement Desensitization and Reprocessing (EMDR; g=0.78, 95% CI [0.71, 0.85], p<.001) and Narrative Exposure Therapy (NET; g=0.71, 95% CI [0.64, 0.78], p<.001). Moderator analysis revealed that the duration of the intervention (β=0.42, p<.001), as well as the severity of trauma at the commencement of treatment (β=0.38, p<.001), significantly influence therapeutic effectiveness. Further network meta-analysis results demonstrated that TF-CBT holds the highest probability of being the most superior intervention (SUCRA=0.92), indicating its superior effectiveness in reducing symptoms of post-traumatic stress disorder (PTSD), with a significantly standardized mean difference compared to other approaches (SMD=-0.45, 95% CI [-0.52, -0.38]). Contrary to findings reported by Korn (2009) and Rahman et al. (2019), which positioned EMDR as the primary method, this study identifies the distinct superiority of TF-CBT specifically for individuals suffering from complex trauma due to prolonged conflict. These results broaden the horizon of prior scientific understanding by emphasizing the importance of trauma-specific characteristics as moderating variables that determine the success of therapeutic interventions.